Manajemen Penggunaan Teknologi untuk Mengukur Kepuasan Kerja Perawat - Fatika Puteri Rosyi Prabowo; Puput Mulyono (Jurnal Kesehatan Amanah, 2024)
The development of innovative health technology continues to be needed by health workers, including nurses in hospitals. Nurses need to adapt and are required to be able to utilize various technological innovations that currently exist. However, the demand for quality services in maintaining patient safety through the use of technology is still a problem that affects the achievement of nurses' job satisfaction. This study aims to describe nurses' job satisfaction regarding the use of health technology. This research is a descriptive study with a cross-sectional design involving 172 hospital nurses. The sample was selected using a purposive sampling method, and data collection was carried out through a questionnaire. Of the nurses in the sample, 33.1% were between 26 and 31 years old, while 90.1% were female. In addition, based on educational background, the majority of nurses (54.1%) had a nursing diploma, and 23.8% had a professional nursing degree. Maximum work experience caring for patients is more than 10 years. The results of this study showed that 40.1% of nurses felt satisfied with the use of health technology, while 59.9% felt dissatisfied. A significant relationship was found between education level, work position, and nurse satisfaction (p <0.05). The recommendation of this study is that the manager's role should include supporting, motivating, and providing self-awareness to nurses regarding technology in order to save time, make communication more effective, facilitate nursing care, and improve patient safety. Managers must also be tasked with implementing technological innovations that are easy to use.